Insulin-like growth factor binding protein-3 (IGFBP-3) mediates vascular repair by enhancing nitric oxide generation - Kielczewski, Jennifer L. (2009)
RATIONALE: Insulin-like growth factor binding protein-3 (IGFBP-3) modulates vascular development by regulating endothelial progenitor cell (EPC) behavior, specifically stimulating EPC cell migration. This study was undertaken to investigate the mechanism of IGFBP-3 effects on EPC function and how IGFBP-3 mediates cytoprotection following vascular injury. OBJECTIVE: To examine the mechanism of IGFBP-3 mediated repair following vascular injury. METHODS AND RESULTS: We utilized two complementary vascular injury models: laser occlusion of retinal vessels in adult GFP chimeric mice and oxygen induced retinopathy (OIR) in mouse pups. Intravitreal injection of IGFBP-3 expressing plasmid into lasered GFP chimeric mice stimulated homing of endothelial precursor cells (EPCs), while reversing ischemia induced increases in macrophage infiltration. IGFBP-3 also reduced the retinal ceramide/sphingomyelin ratio that was increased following laser injury. In the OIR model, IGFBP-3 prevented cell death of resident vascular endothelial cells and EPCs, while simultaneously increasing astrocytic ensheathment of vessels. For EPCs to orchestrate repair, these cells must migrate into ischemic tissue. This migratory ability is mediated, in part, by endogenous nitric oxide (NO) generation. Thus, we asked whether IGFBP-3’s migratory effects were due to stimulation of NO generation. IGFBP-3 increased eNOS expression in human EPCs leading to NO generation. IGFBP-3 exposure also led to the redistribution of vasodilator stimulated phosphoprotein (VASP), a NO regulated protein critical for cell migration. IGFBP-3 mediated NO generation required HDL receptor activation and stimulation of PI3K/Akt pathway. CONCLUSION: These studies support consideration of IGFBP-3 as a novel agent to restore the function of injured vasculature and restore NO generation.